EXPERIENCE OF TREATMENT OF PATIENT WITH JUVENILE SERONEGATIVE POLYARTHRITIS WITH MEDICATION CONTAINING GLUCOSAMINE AND EXTRACTS OF ZINGIBER OFFICINALE - E.Yu. Gudkova; T.М. Bzarova; E.G. Chistyakova; A.O. Lisitsin; E.I. Alexeeva ("Paediatrician" Publishers LLC, 2008)
A case report on a severe course of juvenile seronegative polyarthritis is presented in this article. Successful treatment with «zinaxin» containing glucosamine and extracts of zingiber officinale, made with lipocap technology as an alternative to nonsteroidal anti9inflammatory drugs was performed is patient with developed adverse event to the medicaments (increase of plasma levels of alanine aminotransferase and aspartate amino transferase five times a much compared to norm), combined with quadrotherapy of duodenal ulcer. Patient had a good status, pain syndrome and morning joint stiffness were absent during treatment with «zinaxin with glucosamine» daily and dsintoxication course (2 months) in conditions of withdrawal of immunosuppressive treatment. activity of disease had 0-1 grade according to examination data. Key words: children, juvenile arthritis, pain syndrome.